INCLUSION OF METALLIC, NATURAL AND SYNTHETIC FIBERS TO INCREASE THE MECHANICAL PROPERTIES FOR CONCRETE ARCHITECTURE - MSc. Haidee Yulady Jaramillo; Andres Alfonso Galindo Montero (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This work aims to know how metallic, natural, and synthetic fibers influence the improvement of the mechanical properties of concrete architecture. The object of the study is to collect information that demonstrates, through a qualitative methodology, the behavior of the study fibers. As a result, it was observed that the mechanical properties of the concrete with different fiber dosages modify its behavior, reducing cracking and fissuring. The fibers give a new vision to develop new alternatives for the architectural construction of alternative and innovative projects.